Urban masjid: the heart and soul of Johor Bahru (Masjid Al-Attas) - Muhammad, Muhammad Azmeer; Abdul Majid, Noor Hanita (Kulliyah of Architecture & Environmental Design, International Islamic University Malaysia, 2019)
Urban Masjid is a new concept that will give more space and facilities to tackle current situation faced by Muslim who lives in a city area. This concept is proposed to be implemented in Masjid Al Attas in Johor Bahru, Malaysia to enhance the Masjid spaces and its functionss, as well as to serve the architectural and social needs.